(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The study was designed to study the effect of complex enzyme (Kingzyme®) on performance and carcass yield of broiler chickens fed red sorghum-based diets. Two hundred (200) chicks (day-old) of mixed sex was randomly allotted to five dietary treatments (T1, T2, T3, T4 and T5) supplemented with enzyme complex (Kingzyme®) at the levels of 0.0g, 0.2g, 0.5g, 0.8g and 1.1g kg per Kg of feed respectively in a Completely Randomized Design (CRD). Each treatment was replicated four (4) times to contain ten (10) birds each. Feed and water were provided ad libitum accompanied with standard management procedures for eight weeks. At end of the experiments, eight (8) birds whose body weights are closest to the mean of the group was randomly selected from each treatment (two (2) per replicate) and was fasted overnight to reduce the gut contents and carcass contamination. The birds for each replicate was weighed to determine the live body weight, followed by slaughtering, bleeding, bled weight determination, scalding and wet plucking. The plucked weight was determined followed by evisceration, dressed weight and weighing of internal organs. The weight of the internal organs and length of small, large intestines and caecum was determined. The weights of the internal organ were expressed as the percentage of the dressed weight. Data were analyzed using Statitix Analytical Software, Version 10; and the treatment means were compared using Turkey HSD. There was no significant (P < 0.05) difference across the treatment groups for feed intake and growth performance at both starter and finisher phases respectively. Similarly, carcass characteristics showed no significant (P < 0.05) difference across the dietary treatments. Lungs, gizzard and proventriculus was significantly (P < 0.05) affected across the dietary treatments. Based on the result of the study, it was concluded that Red Sorghum-based diet supplemented with enzyme complex (Kingzyme®) do not have any significant effect on feed intake and growth performance of broiler chickens but can change some internal organs weights especially the lungs, gizzards and proventriculus.